The Impact of Incentives to Recruit and Retain Teachers in “Hard‐to‐Staff” Subjects - Feng, Li; Sass, Tim R. (Journal of policy analysis and management, 2018)
We investigate the effects of a statewide program designed to increase the supply of teachers in designated “hard‐to‐staff” areas, such as special education, math, and science. Employing a difference‐in‐difference estimator we find that the loan forgiveness component of the program was effective, reducing mean attrition rates for middle and high school math and science teachers by 10.4 percent and 8.9 percent, respectively. We also find that the impact of loan forgiveness varied with the generosity of payments; when fully funded, the program reduced attrition of special education teachers by 12.3 percent, but did not have a statistically significant impact when funding was substantially reduced. A triple‐difference estimate indicates that a one‐time bonus program also had large effects, reducing the likelihood of teachers’ exit by as much as 32 percent in the short run. A back‐of‐the‐envelope cost‐benefit analysis suggests that both the loan forgiveness and the bonus program were cost effective.